Copper and zinc thresholds in EU topsoils : Insights from LUCAS and literature datasets - Kiani, Mina; Van Eynde, Elise; Santner, Jakob; Horn, Dietmar; Panagos, Panos; Hernandez-Mora, Alicia; Duboc, Olivier; Eigner, Herbert; Heller, Gereon; Geyer, Stefan; Jones, Arwyn; Ylivainio, Kari (Pergamon press, 2026)
Copper (Cu) and zinc (Zn) are essential micronutrients, critical for both crop growth and human health, yet imbalances can result in deficiency or toxicity. Assessments based on total metal concentrations miss key insights into metal bioavailability and mobility. This study addresses the existing gap in data and knowledge on readily available Cu and Zn in EU agricultural soils. We used a subset of the Land Use and Coverage Area frame Survey (LUCAS) topsoil database in 2015 to map distributions of available Cu and Zn in agricultural soils across the EU27 + UK using the electro-ultrafiltration (EUF) technique. The EUF results made it possible to identify reigons where agricultural soils may require Cu and Zn fertilization or face toxicity risks. Using existing thresholds from the Austrian fertilization guideline, around one-third (32%) of the soils were deficient in Cu, mainly in Northern and Eastern Europe, while Zn deficiency affected 14% of samples, notably in Spain, Cyprus, and Finland. Only a small proportion (1.5%) of samples exceeded the estimated Cu toxicity threshold. Overall, our findings indicate that continental regions consistently exhibit higher available Cu and Zn levels than Northern Europe, where igneous parent materials and less weathered glacial soils prevail. In addition, in Southern and Eastern Europe and inland regions of Spain, where calcareous soils are common, low Zn availability was observed. While natural factors largely explain these regional differences, local anthropogenic activities further contribute to elevated metal concentrations. Our results contribute to the monitoring of soil Cu and Zn beyond total concentrations, helping guide fertilization practices that support optimal crop nutrition and ensure safe and nutritious food.
Keywords: EUF technique; food nutrition; food safety; geochemical mapping; micronutrient deficiency; soil contamination